Excavated octahedral Pt-Co alloy nanocrystals built with ultrathin nanosheets as superior multifunctional electrocatalysts for energy conversion applications. (September 2017) - Chen, Qiaoli; Cao, Zhenming; Du, Guifen; Kuang, Qin; Huang, Jin; Xie, Zhaoxiong; Zheng, Lansun
Abstract: Pt-Co alloy is thought to be the best potential catalyst toward many electrocatalytic energy conversion reactions among various bimetallic alloys. To optimize the performance and reduce the usage of noble metal Pt, both the mass and surface contribution should be considered, which requires Pt-Co alloy nanocrystals (NCs) to possess large surface area and expose specific facets. Unfortunately, these requirements can hardly be met simultaneously for the NCs with normal convex polyhedral shapes. In this work, a simple cetyltrimethylammonium bromide-assisted method is proposed to controllably synthesize Pt-Co alloy NCs with a unique excavated octahedral shape. The excavated octahedral Pt-Co alloy NCs is intrinsically built with mutually perpendicular interlaced ultrathin PtCo nanosheets bound with {100} facets that are not the thermodynamically most stable for face-centered cubic metals. The electrochemically surface area of the unique excavated octahedral PtCo alloy NCs is determined to be 23.3 m 2  g −1 Pt, which is significantly larger than that of the normal octahedral Pt2 Co alloy NCs with the same size (11.4 m 2  g −1 Pt ). Owing to the combination of large surface area and high active {100} facets, the excavated octahedral PtCo NCs display extraordinary catalytic activity and durability towards hydrogen evolution reaction in alkaline environment. Strikingly, the overpotential of excavated PtCo NCs at the current density of 20 mA cm −2 is as low as 76.2 mV, which is much lower than that for the {111} faceted Pt2 Co NCs (83.9 mV) and the commercial Pt/C (107 mV), respectively. Besides, the excavated octahedral PtCo NCs also show significantly enhanced electrocatalytic performances towards methanol oxidation reaction and oxygen reduction reaction when both considering the mass and surface contribution. Graphical abstract: Highlights: Excavated octahedral PtCo NCs with specific facets and large surface area were synthesized. The surfactant and growth kinetics affects the composition and morphology of PtCo NCs. Excavated PtCo NCs showed superior performance as multifunctional electrocatalysts.